Application Development Design “How To Make Money Online” Using The Wartefall Method (Case Study : CV Satoeasa For Indonesia) - Agil Setyo Prasandi; Tikaridha Hardiani (Universitas Muhammadiyah Sidoarjo, 2021)
CV Satoeasa is a organization engaged in training and consulting services in the context of empowering and developing business actors. Satoeasa is supported by personnel who have competency standards and experience in the fields of entrepreneurship and local economic development. CV Satoeasa Untuk Indonesia is committed to increasing entrepreneurial capacity and is passionate about realizing a growing and developing business. use of the application